Quantitative assessment of visual behavior in disorders of consciousness - Trojano, L.; Moretta, P.; Loreto, V.; Cozzolino, A.; Santoro, L.; Estraneo, A. (Journal of neurology, 2012)
The study of eye behavior is of paramount importance in the differential diagnosis of disorders of consciousness (DoC). In spite of this, assessment of eye movement patterns in patients with vegetative state (VS) or minimally conscious state (MCS) only relies on clinical evaluation. In this study we aimed to provide a quantitative assessment of visual tracking behavior in response to moving stimuli in DoC patients. Nine VS patients and nine MCS patients were recruited in a Neurorehabilitation Unit for patients with chronic DoC; 11 matched healthy subjects were tested as the control group. All participants underwent a quantitative evaluation of eye-tracking pattern by means of a computerized infrared eye-tracker system; stimuli were represented by a red circle or a small color picture slowly moving on a PC monitor. The proportion of on- or off-target fixations differed significantly between MCS and VS. Most importantly, the distribution of fixations on or off the target in all VS patients was at or below the chance level, whereas in the MCS group seven out of nine patients showed a proportion of on-target fixations significantly higher than the chance level. Fixation length did not differ among the three groups significantly. The present quantitative assessment of visual behaviour in a tracking task demonstrated that MCS and VS patients differ in the proportion of on-target fixations. These results could have important clinical implications since the quantitative analysis of visual behavior might provide additional elements in the differential diagnosis of DoC.